Role of curcumin in altering gut microbiota for anti-obesity and anti-hyperlipidemic effects - Feng, Jingxi (Frontiers in Microbiology, 2025)
Obesity significantly impacts the health and economy of modern society, and the prevention and treatment of obesity is a key focus of social research. The main reason for obesity is the excessive accumulation of body fat due to metabolic dysfunction, which may result in atherosclerosis, insulin resistance and abnormal lipid metabolism. So far, a number of mechanisms of intestinal flora and plant extracts have been found and applied to the treatment of obesity. However, because of the complexity of gut microbiota composition, it is still not clear which microbiota has a direct relationship with obesity. Curcumin (CUR) has a long-standing and important position in traditional Chinese medicine (TCM). It is a polyphenolic compound derived from the rhizome of Curcuma longa. CUR has been widely studied in recent years for its multiple biological activities. In addition to its anti-inflammatory and antioxidant properties, CUR also shows potential in anti-cancer, anti-microbial, and neuroprotective effects. This review aims to systematically synthesize the current evidence on the effects and mechanisms of CUR targeting gut microbiota in obesity treatment, analyze the progress of CUR research in fat reduction and weight loss, and specifically clarify its role in modulating gut microbiota to exert both anti-obesity and anti-hyperlipidemic effects. By doing so, we seek to illuminate the intricate relationship between CUR, gut microbiota, and obesity with associated hyperlipidemia.